The Effect of Transformational Leadership Style and Organizational Innovation on Improving Environmental Performance of Environmental Polluters Companies Case Study: Lead Producer Companies in Zanjan Province - PIRAYESH, Reza; POURREZAY, Zahra (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019, 2020)
The need for an appropriate leadership style that can regulate and improve the organization's culture to improving environmental performance is vital to the success of the organization. New developments in leadership theories have moved from charismatic leadership theories to neo-charismatic and transformational leadership theories. This study was carried out aimed to investigate the effect of transformational leadership style and organizational innovation on improving environmental performance of environmental polluters companies Zanjan Province in Iran. The research method was descriptive survey. The data collection tool was a standard questionnaire. The statistical population of this study was 5 Lead producer company in Zanjan. The questionnaires were distributed randomly among 317 persons of statistical samples. The conceptual model of the research was fitted using the structural equation model in PLS software. Research findings have shown that transformational leadership and organizational innovation has an impact on improving environmental performance.